Representations of gender, respectability and commercial sex in the shadow of AIDS: a South African case study - Campbell, Catherine (1998)
This paper seeks to illustrate the way in which social representations of gender shape the sexual behaviour of female commercial sex workers selling sex to migrant workers on the South African mines. The paper examines strategies used by women to maintain a sense of gendered respectability in spite of their involvement in a stigmatized profession, strategies involving denial, justification and an appeal to alternative identities. Attention is given to the way in which such strategies undermine women's confidence to insist on condom use in the face of client reluctance. The implications of such representations and strategies for HIV prevention are discussed. - Reproduced
Keywords: Case studies; Aids - South Africa; Aids